REVISITING ENGLISH PROFICIENCY AND ITS POLICY IN HIGHER EDUCATION: THE CASE OF THE UNIVERSITY OF RIAU - Muryanti Muryanti; Daeng Ayub Natuna; Viony Syafitra; Wilasari Arien (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2023)
The rapid change in today’s society forces higher education to adapt to it and transform to prepare their graduates for the future, which entails regulating minimum language proficiency levels for a graduation requirement in universities. This study aims to investigate university students’ English proficiency level to revisit English language requirements at higher education institutions. To do so, this study used simple descriptive research using a TOEFL Prediction test administered to 400 university students at the University of Riau. The score was converted to the Common European Framework of Reference for Language (CEFR) to investigate whether the scores are relevant to the university’s needs. The results show that the majority of students (N=258) have achieved the A2 CEFR level (Basic User – way stage). This suggests that it has fulfilled the minimum requirement set by the university. However, this is unlikely to reflect the objectives envisioned by the institution. Therefore, recommendations aroused from the findings will be provided in this research.